Renal Transplantation with Kidneys Affected by Tumours. (28th December 2010) - Khurram, Muhammad Arslan; Sanni, Aliu Oladipupo; Rix, David; Talbot, David
Abstract : Renal transplantation confers improvement in quality of life and survival when compared to patients on dialysis. There is a universal shortage of organs, and efforts have been made to overcome this shortage by exploring new sources. One such area is the use of kidneys containing small tumours after resection of the neoplasm. This paper looks at the current evidence in the literature and reviews the feasibility of utilizing such a source.